A Scoping Review: Faktor Penyebab Pending Klaim BPJS Kesehatan Rawat Inap di Rumah Sakit - Hindun Mursyid; Sri Rahayub; Vican Sefiany Koloic (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
Pending claims for Indonesian Universal Health Coverage (BPJS Kesehatan) is a classic issue in the field of health budgeting in the National Health Security (JKN) era. Some studies have examined factors causing pending claims, however, the issue has not been figured out yet because every hospital has different problems. This study was conducted to identify the problems possibly causing pending claims faced by hospitals. The objectives of the study were to find out the factors causing inpatient pending claims for BPJS Health Insurance at the hospital.  The article search method begins by identifying research articles on two databases, Google Scholar and Academia.edu with predetermined keywords. Articles are selected by PRISMA and based on established inclusion and exclusion criteria. The search results obtained 191 articles identified from two database searches, including 151 articles from Google Scholar and 40 articles from Academia.edu, finally, only 9 articles were obtained that matched the criteria. Pending claims for inpatient BPJS Health Insurance at the hospital under study were caused by several problems including inaccuracy in coding, incomplete administrative files, not attaching the results of supporting examinations as a support for the diagnosis, enforcement of diagnoses that did not meet the criteria, different perceptions of standard enforcement of diagnoses between specialist and BPJS, different points of view regarding the diagnosis code between hospital coding officers and BPJS verifiers, the discrepancy between main diagnoses and specialist, incomplete medical resumes, there is no SOP for managing BPJS Health insurance claims, knowledge of claim executors, facilities and infrastructure in the claims section, wrong input on the claim application. Managerial support is tremendously required to solve the issues related to pending claims for BPJS Kesehatan.